The role of Indonesian government in middle east conflict resolution: consistent diplomacy or strategic shifts? - Setiawati, Siti Mutiah (Frontiers in Political Science, 2024)
Indonesia and Middle Eastern countries are associated with a shared characteristic in the form of Islam, despite the geographical separation and cultural and ethnic distinctions. Since gaining independence in 1945, Indonesia has consistently advocated for the peaceful resolution of conflict in the Middle East, including the Palestinian/Arab–Israeli conflict. Therefore, the objective of this study was to explore the motivations behind Indonesia’s consistent support for Middle Eastern conflict resolution. Although the Indonesian government is eager to advance its involvement in the conflict resolution process, it is also compelled by the constitution to uphold the “Free and Active” foreign policy axiom, which essentially restricts Indonesia from taking on a side, maintaining cordial ties with the parties involved. These principles prevent Indonesia from favoring one side and maintaining positive relations with both conflicting parties. Indonesia has often played a passive role as a facilitator or participant in conflict resolution attempts rather than actively taking on the role of a mediator. Indonesia’s unwavering commitment to resolving the Middle East conflict largely originates from Islamic solidarity with a predominantly Muslim population in the region and a shared identity as a fellow developing country, rather than being solely based on its constitution. Alternatively, this sense of unity may also stem from the notion of solidarity within the Global South.